2016
DOI: 10.3402/pba.v6.33276
|View full text |Cite
|
Sign up to set email alerts
|

Multiple morbidities in companion dogs: a novel model for investigating age-related disease

Abstract: The proportion of men and women surviving over 65 years has been steadily increasing over the last century. In their later years, many of these individuals are afflicted with multiple chronic conditions, placing increasing pressure on healthcare systems. The accumulation of multiple health problems with advanced age is well documented, yet the causes are poorly understood. Animal models have long been employed in attempts to elucidate these complex mechanisms with limited success. Recently, the domestic dog ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
6
28
0
Order By: Relevance
“…These phenomena allow researchers not only to study the pathologies that influence mortality, but also to understand different comorbidities and multiple chronic conditions that canines exhibit. In previous work, we showed that multimorbidity in the dog increases with age (Jin, Hoffman, Creevy, O'Neill & Promislow, 2016), similar to patterns seen in humans. As we discuss here, the domestic dog could be a useful model to understand how comorbidities, both as cause and consequence, are associated with aging in humans.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…These phenomena allow researchers not only to study the pathologies that influence mortality, but also to understand different comorbidities and multiple chronic conditions that canines exhibit. In previous work, we showed that multimorbidity in the dog increases with age (Jin, Hoffman, Creevy, O'Neill & Promislow, 2016), similar to patterns seen in humans. As we discuss here, the domestic dog could be a useful model to understand how comorbidities, both as cause and consequence, are associated with aging in humans.…”
Section: Introductionsupporting
confidence: 74%
“…Our multimorbidity analysis suggests that companion dogs have the potential to be an excellent model to better understand the causes and consequences of multiple chronic conditions as we age. Similar to previous results reported by our laboratory (Jin et al., 2016), multimorbidity (total number of diagnoses recorded at the time of death) increases with age in the dog as is seen in human populations (Fortin, Bravo, Hudon, Vanasse & Lapointe, 2005). In addition, comorbidities vary significantly among different chronic conditions in the dog (Figure 3).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations